2020
DOI: 10.1128/jb.00301-20
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of VirB6 Paralogs in Anaplasma phagocytophilum Attenuates Its Growth

Abstract: Many pathogenic bacteria translocate virulence factors into their eukaryotic hosts by means of Type 4 Secretion Systems (T4SS) spanning the inner and outer membranes. Genes encoding components of these systems have been identified within the Order Rickettsiales based upon their sequence similarities to other prototypical systems. Anaplasma phagocytophilum are obligate intracellular, tick-borne bacteria that are members of this Order. The organization of these components at the genomic level was determined in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…As it is known that transposon insertions can have polar effects on adjacent genes [ 32 , 34 , 35 ], primers were designed to amplify cDNA of portions of 3 genes located downstream of sca1 , RF_0023 , RF_0024 , and RF_0025 ( S1A Fig ). Of interest, only transcripts from RF_0023 were detected in R .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is known that transposon insertions can have polar effects on adjacent genes [ 32 , 34 , 35 ], primers were designed to amplify cDNA of portions of 3 genes located downstream of sca1 , RF_0023 , RF_0024 , and RF_0025 ( S1A Fig ). Of interest, only transcripts from RF_0023 were detected in R .…”
Section: Resultsmentioning
confidence: 99%
“…As it is known that transposon insertions can have polar effects on adjacent genes [32,34,35], primers were designed to amplify cDNA of portions of 3 genes located downstream of sca1, RF_0023, RF_0024, and RF_0025 (S1A Fig) . Of interest, only transcripts from RF_0023 were detected in R. felis WT, where the absence of transcripts was observed for R. felis sca1::tn (S1B Fig) . No amplification of rickettsial DNA was detected in no reverse transcriptase controls. Thus, the data suggests the Himar1 insertion has altered sca1 gene transcription and subsequently affected transcription of a neighboring gene.…”
Section: Himar1 Transposon Interrupts Normal Gene Transcription Of Sca1mentioning
confidence: 99%
“…As a control strain, we used another mutant, which contains the Himar1 transposon in an intergenic location. This strain has been shown to be phenotypically equivalent to wild-type A. phagocytophilum (27, 28). Our analysis confirmed that transcription of ateA was abolished in the ateA ::Himar1 mutant, but transcription of housekeeping genes, rpoB and groEL , and the conserved Anaplasma gene encoding major surface protein 5, msp5 , were all unaffected (Figure 1B).…”
Section: Resultsmentioning
confidence: 98%
“…We therefore used qRT-PCR with primers targeting non-repetitive sequences to quantify ateA expression patterns from A. phagocytophilum grown in HL60 and ISE6 cells. Housekeeping A. phagocytophilum genes, rpoB and groEL , are equally expressed when grown in either mammalian or tick cell lines (7, 27), and were therefore used as baseline controls for expression. Our findings demonstrate that ateA expression was >8 fold higher during growth in tick cells than in mammalian cells (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation